Prevalence and antimicrobial susceptibility patterns of Vibrio cholerae in dairy excreta - Eashmen, Nilofa; Arif, Mohammad; Sarker, Basana; Akter, Mir Rowshan; Kabir, S M Lutful (Asian-Australasian Journal of Bioscience and Biotechnology, 2021)
Vibrio cholerae is a major etiological agent of human diarrhoea and has become epidemic across the world in the recent past. A cross-sectional study was conducted to assess the prevalence of V. cholerae from dairy excreta along with antimicrobial resistant status of the isolates. A total 50 samples were collected from 50 different household manure pit located at Bangladesh Agriculture University (BAU) surrounding area, Mymensingh. Alkaline peptone water was used for enrichment of the samples followed by inoculation onto thiosulfate citrate bile salt sucrose (TCBS) agar media for the isolation of Vibrio spp., which were further confirmed via Vibrio genus specific molecular assay. Biochemical tests were performed to identify V. cholerae from the isolates of Vibrio spp. Out of 50 samples 17 (34%) were confirmed as Vibrio spp. as they produced characteristic yellow colonies on TCBS agar and had found to possess recombinase A gene that confirmed the identity of Vibrio spp. From this 17 Vibrio isolates, 6 (12% in total from 50 samples) were identified as V. cholerae based on different biochemical tests. All the isolates fermented glucose, maltose, sucrose and mannitol with the production of only acid. The isolates were positive in oxidase, gelatinase, methyl-red (MR) and indole test, but negative in case of voges-proskaure (VP) test. In antimicrobial susceptibility testing, V. cholerae isolates showed 100% sensitivity to gentamycin, chloramphenicol and tetracycline with moderate sensitivity to ciprofloxacin and co-trimoxazole. A high level of resistance was observed to ampicillin (100%) followed by moderate resistance to erythromycin and imipenem. In the present study about 33.33% (n = 2) of 6 isolated V. cholerae were found to be multidrug resistant (MDR) as they demonstrated resistant against 3 antimicrobial agents. The findings of this study substantiate the presence of MDR V. cholerae in the dairy excreta, which indicates the role of domestic animals to serve as a reservoir that might pose a health risk to human. Hygienic management of animal waste is needed to reduce the burden of human illness. Asian Australas. J. Biosci. Biotechnol. 2021, 6 (1), 40-49